1990
DOI: 10.1152/ajpendo.1990.259.3.e327
|View full text |Cite
|
Sign up to set email alerts
|

Systemic pH modifies ketone body production rates and lipolysis in humans.

Abstract: To investigate whether changes in systemic pH influence ketone body production or utilization, total ketone body (TK) kinetics were measured with [3-14C]acetoacetate and D-beta-[1,3-13C2]hydroxybutyrate tracers in overnight fasted subjects during metabolic alkalosis (NaHCO3 infusion) or acidosis [NH4Cl ingestion or arginine (Arg)-HCl infusion]. Somatostatin, with insulin, glucagon, and growth hormone replacement, was infused in all studies. Blood pH and HCO3- (mM) increased from baseline (0-30 min) to 180-210 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The rate of lipolysis is controlled by several factors [11,12]; one of the most well-known factors is pH [13]. It has been demonstrated that plasma FFA concentration decreases during acidosis, whereas alkalosis results in an increase in plasma FFA [14,15]. Recently, the buffering properties of NaP have been widely reviewed [16].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of lipolysis is controlled by several factors [11,12]; one of the most well-known factors is pH [13]. It has been demonstrated that plasma FFA concentration decreases during acidosis, whereas alkalosis results in an increase in plasma FFA [14,15]. Recently, the buffering properties of NaP have been widely reviewed [16].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome GLP-1-induced hormonal changes, somatostatin was infused during all studies, while insulin, glucagon and growth hormone were replaced in basal amounts (pancreatic clamp) [9]. Glucose clamping was performed at 8 mmol/l taking into account the glucose dependence of GLP-1 effects and imitating mild hyperglycemia during restricted insulin availability.…”
Section: Introductionmentioning
confidence: 99%
“…[1-13 C]-Leucine infusions were used to measure leucine flux and oxidation as parameters of whole-body protein breakdown and catabolism [15], and indirect calorimetry yielded energy expenditure data. In order to differentiate between insulin-mediated and direct GLP-1 effects, similar experiments were performed during somatostatin infusion blocking pancreatic hormone secretion (pancreatic clamp) [16]. Considering the glucose dependence of the GLP-1 effects, all the experiments were performed during hyperglycaemic glucose clamping.…”
Section: Introductionmentioning
confidence: 99%